2019
DOI: 10.1039/c9cp03520f
|View full text |Cite
|
Sign up to set email alerts
|

How membrane lipids influence plasma delivery of reactive oxygen species into cells and subsequent DNA damage: an experimental and computational study

Abstract: The combination of phospholipid vesicle experiments and molecular dynamics (MD) simulations illustrate how lipid oxidation, lipid packing and rafts formation may influence the response of healthy and diseased cell membranes to plasma-derived RONS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 73 publications
(77 reference statements)
1
23
0
Order By: Relevance
“…Some of these factors include cancer cells generally having a higher number of aquaporin channels and altered levels of certain lipid types and cholesterol in such a way that these features reduce the barrier effects of the cell membrane to ROS [8][9][10][11][12]. These features allow cancer cells to easily uptake plasma generated ROS in certain circumstances, which makes these cells more susceptible to oxidative damage by the plasma treatment [13][14][15]. Plasma induced oxidative stress may also disrupt biomolecular binding events to inhibit proliferative signalling pathways in cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors include cancer cells generally having a higher number of aquaporin channels and altered levels of certain lipid types and cholesterol in such a way that these features reduce the barrier effects of the cell membrane to ROS [8][9][10][11][12]. These features allow cancer cells to easily uptake plasma generated ROS in certain circumstances, which makes these cells more susceptible to oxidative damage by the plasma treatment [13][14][15]. Plasma induced oxidative stress may also disrupt biomolecular binding events to inhibit proliferative signalling pathways in cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…As reported by van der Paal et al, [37] the ROS generated by the plasma could pass through cell membranes, which contain unsaturated lipids or cholesterol. The dead keratinocytes and lipid matrix of SC contain abundant unsaturated lipids and cholesterol.…”
Section: The Effect Of Ros On Tdd Efficiencymentioning
confidence: 76%
“…For plasma medicine, molecules involved in this process might be related to, for instance, the Nrf2 pathway [ 36 , 74 , 75 ], heme oxygenase 1 (HMOX1) [ 76 ], or other antioxidant response elements [ 77 ]. Others have suggested that the lipid composition of tumor cells [ 78 , 79 , 80 ] and the expression of aquaporins [ 81 , 82 , 83 ] are also important for the selectivity of plasmas towards malignant cells. Plasma generates different ROS, such as ozone (O 3 ), superoxide (O 2 − ), singlet delta oxygen ( 1 O 2 ), atomic oxygen (O), hydroxyl radical ( • OH), and hydrogen peroxide (H 2 O 2 ) [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%